PERFORMANCE AND ENERGY SAVING EVALUATION OF SOLAR ABSORPTION REFRIGERATION SYSTEMS IN NORTHEASTERN ALGERIA - Zoheir Derghout,; Lotfi Ziani,; Abdelhafid Gherfi,; Djamila Rouag, (International Journal of Innovative Technologies in Social Science, 2024)
The global energy demand and environmental concerns rise, solar absorption refrigeration systems present a sustainable alternative to conventional cooling technologies. This study aims to evaluate the performance of a solar absorption refrigeration machine in Constantine (North-East Algeria), focusing on its efficiency and suitability for the region's climate. This region, known for its high temperatures and abundant solar radiation, offers an ideal setting to study these systems. The Aspen software is employed to simulate the absorption refrigeration system without solar collectors. Empirical equations were developed, and a Python code was used to integrate a solar thermal collector and calculate overall Coefficients of Performance (COPs) for the air conditioning mode. The system utilized water and lithium bromide as working fluids. Setting an indoor temperature at 25°C, hourly outdoor temperatures and solar radiation data for Constantine from May to October are provided by Meteonorm software (version 7). The present investigation revealed that Constantine's summer monthly solar irradiation reaches up to 220 KWh/m2, making the region highly suitable for solar-powered cooling. The system demonstrated promising performance and energy saving, with COP ranging from 0.75 to 0.89 and COPs between 0.57 and 0.63. Likewise, it also confirms the feasibility of solar absorption refrigeration systems in high-temperature, high-solar-radiation regions like Constantine, Algeria. The observed performance metrics suggest significant potential for sustainable cooling solutions in similar climates and will influence how cities are designed and built, especially in hot climates. This type of system mitigates climate change. Future research should focus on integrating advanced solar collectors and optimizing system design to enhance efficiency and cost-effectiveness.